ISSUES ON SCIENTIFIC RESEARCH IN PLACES OF HOLDING - Ioan CHIŞ; Oana Alexandra CHIŞ (Challenges of the Knowledge Society)
Scientific research in prisons is not a new problem. New is the way of granting benefits to persons who show such while serving sentences of imprisonment. Some shortcomings in establishing the criteria, rules and way of determining the authors, led to the emergence in 2016 of over 300 works published under the name of condemned authors.